ABCC Transporters Mediate the Vacuolar Accumulation of Crocins in Saffron Stigmas. Issue 11 (23rd September 2019) - Demurtas, Olivia Costantina; de Brito Francisco, Rita; Diretto, Gianfranco; Ferrante, Paola; Frusciante, Sarah; Pietrella, Marco; Aprea, Giuseppe; Borghi, Lorenzo; Feeney, Mistianne; Frigerio, Lorenzo; Coricello, Adriana; Costa, Giosuè; et al.
Abstract : A transportomics approach allows identification of crocin vacuolar transporters from saffron stigmas. Abstract: Compartmentation is a key strategy enacted by plants for the storage of specialized metabolites. The saffron spice owes its red color to crocins, a complex mixture of apocarotenoid glycosides that accumulate in intracellular vacuoles and reach up to 10% of the spice dry weight. We developed a general approach, based on coexpression analysis, heterologous expression in yeast ( Saccharomyces cerevisiae ), and in vitro transportomic assays using yeast microsomes and total plant metabolite extracts, for the identification of putative vacuolar metabolite transporters, and we used it to identify Crocus sativus transporters mediating vacuolar crocin accumulation in stigmas. Three transporters, belonging to both the multidrug and toxic compound extrusion and ATP binding cassette C (ABCC) families, were coexpressed with crocins and/or with the gene encoding the first dedicated enzyme in the crocin biosynthetic pathway, CsCCD2. Two of these, belonging to the ABCC family, were able to mediate transport of several crocins when expressed in yeast microsomes. CsABCC4a was selectively expressed in C. sativus stigmas, was predominantly tonoplast localized, transported crocins in vitro in a stereospecific and cooperative way, and was able to enhance crocin accumulation when expressed in Nicotiana benthamiana leaves.